PENGARUH MANAJEMEN WAKTU DAN PEMANFAATAN SUMBER BELAJAR TERHADAP PRESTASI BELAJAR MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI FKIP UNIVERSITAS RIAU - Arif Firman Syaputra; Suarman Suarman; Gani Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the effect of time management and utilization of learning resources on the learning achievements of Economics Education Study Program Students at FKIP Riau University. The population in this study were students of Economic Education Study Program FKIP Riau University generation 2015 and 2016 as many as 164 people, the sample was determined using the Issac Table of 105 people and sample selection was determined by Proportional Random Sampling technique. The results showed that time management and utilization of learning resources had a positive and significant effect on learning achievement both partially and simultaneously with a contribution of 56.9% while the remaining 43.1% was influenced by other factors not examined in this study namely learning motivation, learning independence, and ability critical thinking. Thus, to improve student learning achievement can be done by improving the implementation of time management, and optimizing the use of learning resources both available inside and outside the campus.Key Words: Time Management, Utilization Of Learning Sources , Learning Achievements